ANALISIS PENGARUH PENGETAHUAN PERPAJAKAN, SOSIALISASI, PELAYANAN, SANKSI PERPAJAKAN, DAN TINGKAT PENDIDIKAN WAJIB PAJAK TERHADAP KESADARAN WAJIB PAJAK MEMBAYAR PBB P2 - Yunita Isna Ratri; Achmad Tjahjono (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2019)
The Analysis Influence of Knowledge Taxation, Socialization, Service, Tax Sanctions and Education Level of Taxpayer Awareness Paying PBB P2. SkripsiStarta One (S1) Accounting Departement STIE Widya Wiwaha Yogyakarta 2018. The purpose of this research is to know influence of Knowledge Taxation,Socialization, Service, Tax Sanctions and Education Level of Taxpayer Awareness Paying PBB P2 with using multiple linear regression and dummy’s variable. The sample in this research includes 120 respondences who are in the District of Prambanan, village Bokoharjo, Madurejo, Sambirejo, Sumberharjo, Wukirharjo, Gayamharjo. The sampling method is convenience sampling. The collected of data to use primary data with questionnaire technique and secondary data that is data taken from DPPKAD (Dinas Pendapatan Pengelolaan Keuangan Aset Daerah). The results of the research to drawn that the partial, knowledge taxation has a positive relationship and significantly influence the awareness of paying taxpayers PBB P2, and Services have a positive relationship and significant effect on the awareness of paying taxpayers PBB P2. By mutual independentvariables affect the awareness of paying taxpayers PBB P2 as a dependent variable.